Developing a Culture of Tolerance Through Islamic Religious Education - Zainal Abidin Muhja; Liza Shahnaz (LETIGES, 2026)
The increasing phenomenon of intolerance in educational environments threatens social harmony in Indonesia's multicultural society. Islamic Religious Education (PAI) plays a strategic role in instilling the values ​​of humanity, tolerance, and peace among people. This study aims to develop and analyse a tolerance-based PAI learning model as a strategy to strengthen the moderate character of students at Madrasah Hurrasul Aqidah, Tarakan. The researcher used a qualitative approach with a case study type. The primary data sources of the study consisted of PAI teachers, the principal, and students. Meanwhile, secondary data sources were obtained from syllabus documents, school archives, and scientific literature related to PAI learning and tolerance education. Data collection techniques included participant observation and semi-structured interviews to explore respondents' perceptions and experiences more flexibly. Data analysis used the Miles and Huberman interactive model through three stages: data reduction, data presentation, and conclusion drawing/verification. Data validity was tested using source and technique triangulation by comparing the results of observations, interviews, and documentation to ensure data validity and reliability. The model for developing Islamic Religious Education (PAI) learning based on culture and tolerance involves creating a syllabus that integrates four main pillars of values: peace, inclusivity, wisdom, and pluralism. The results of the study indicate that the implementation of a culture- and tolerance-based syllabus has a positive impact on increasing students' empathy and openness in interacting with friends of different religions. Furthermore, learning strategies involving discussions, simulations, case studies, and contextual learning have proven effective in fostering social empathy, respect for differences, and student discipline and responsibility. The limitation of this study is its limited scope in one location, so the results cannot be generalised widely. Nevertheless, these findings provide an important contribution to strengthening the paradigm of humanistic and multicultural religious education in Indonesia.